A closed-tube loop-mediated isothermal amplification assay for the visual endpoint detection of Brucella spp. and Mycobacterium avium subsp. paratuberculosis - Trangoni, Marcos David (2017)
LAMP (loop-mediated isothermal amplification) is an isothermal nucleic acid amplification technique that is characterized by its efficiency, rapidity, high yield of final product, robustness, sensitivity, and specificity, with the blueprint that it can be implemented in laboratories of low technological complexity. Despite the conceptual complexity underlying the mechanistic basis for the nucleic acid amplification, the technique is simple to use and the amplification and detection can be carried out in just one step. In this chapter, we present a protocol based on LAMP for the rapid identification of isolates of Brucella spp. and Mycobacterium avium subsp. paratuberculosis, two major bacterial pathogens in veterinary medicine.